2013
DOI: 10.1094/pdis-10-12-0942-re
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivation and Timing of Nitrogen Fertilization on Large Patch Disease of Zoysiagrass

Abstract: Obasa, K., Fry, J., St. John, R., and Kennelly, M. 2013. Effect of cultivation and timing of nitrogen fertilization on large patch disease of zoysiagrass. Plant Dis. 97:1075-1081.Large patch of zoysiagrass (Zoysia spp.) is caused by Rhizoctonia solani anastomosis group 2-2 LP. The effects of summer cultivation (core-aerification, verticutting, and sand topdressing) and spring and fall versus summer nitrogen (N) fertilization on large patch in fairway height 'Meyer' zoysiagrass were investigated from 2008 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…This result supports previous research indicating N applications during the large patch infection period do not increase large patch severity and may in fact reduce it (Obasa et al, 2013;Miller et al, 2016). This result supports previous research indicating N applications during the large patch infection period do not increase large patch severity and may in fact reduce it (Obasa et al, 2013;Miller et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This result supports previous research indicating N applications during the large patch infection period do not increase large patch severity and may in fact reduce it (Obasa et al, 2013;Miller et al, 2016). This result supports previous research indicating N applications during the large patch infection period do not increase large patch severity and may in fact reduce it (Obasa et al, 2013;Miller et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Green et al (1994) found that summer urea rates did not affect large patch severity, and there was no significant difference in disease severity between summer-applied synthetic and natural N sources. Spring and fall urea applications were associated with decreased large patch severity compared with summer standard urea applications (Obasa et al, 2013). In another study, separate fall and spring N applications did not increase large patch severity compared with summer-only N applications (Miller et al, 2016).…”
mentioning
confidence: 86%
See 3 more Smart Citations